Arcuate Uterus as an Independent Risk Factor for Adverse Pregnancy Outcomes - Connolly, Courtney T.; Hill, Melissa B.; Klahr, Rebecca A.; Zafman, Kelly B.; Rebarber, Andrei; Fox, Nathan S. (American Journal of Perinatology, 2021)
Objective The aim of the study is to estimate the association between arcuate uterus and pregnancy outcomes using controls selected from a similarly high-risk cohort.Study Design This is a retrospective cohort study of women with an arcuate uterus cared for by a single maternal–fetal medicine practice from 2005 to 2020. We included all women with a singleton pregnancy ≥20 weeks and diagnosis of arcuate uterus and randomly selected (3:1) patients with a singleton pregnancy and no uterine anomaly from the same practice as controls. Baseline characteristics and pregnancy outcomes were compared between the two groups. Chi-square, Fisher's exact, and independent samples t-test were used for data analysis, as indicated.Results A total of 37 women with an arcuate uterus (55 independent singleton pregnancies) and 165 controls were included. There were no differences in baseline characteristics. Women with an arcuate uterus had a significantly higher rate of spontaneous preterm birth less than 37 weeks (10.9 vs. 3.0%, p = 0.031) and were more likely to require vaginal progesterone (5.5 vs. 0.6%, p = 0.049) and administration of antenatal corticosteroids (16.4 vs. 5.5%, p = 0.020). Arcuate uterus was also associated with lower birthweight (3,028.1 ± 528.0 vs. 3257.2 ± 579.9 g, p = 0.010) and higher incidence of intrauterine fetal growth restriction (20.0 vs. 7.3%, p = 0.008), despite similar starting body mass index (BMI) and weight gain throughout pregnancy. There were no differences in preeclampsia, malpresentation, cesarean delivery, blood transfusion, retained placenta, or morbidly adherent placenta.Conclusion Arcuate uterus is associated with a significantly increased risk of spontaneous preterm birth (<37 weeks), need for vaginal progesterone for short cervix and antenatal corticosteroids, fetal growth restriction, and lower mean birthweight. These findings suggest that arcuate uterus is not just a normal variant of uterine anatomy but rather a risk factor for poor fetal growth, short cervix, and a higher risk pregnancy.Key Points
Keywords: arcuate uterus; uterine anomaly; preterm birth; fetal growth restriction